Evaluating compliance of extended venous thromboembolism prophylaxis following abdominopelvic surgery for cancer: A multidisciplinary quality improvement project. Issue 3 (22nd October 2021) - McGinnis, Justin M.; Helpman, Limor; Gundayao, Marylrose; Nancekivell, Kelly‐Lynn; Russell, Jacqueline; Linkins, Lori‐Ann; Ruo, Leyo; Serrano, Pablo E.
Abstract: Background and Objectives: Despite quality evidence supporting postoperative extended venous thromboembolism prophylaxis (eVTEp) following abdominopelvic cancer surgery, baseline use of eVTEp at our institution was 3%. Our project aim was to improve the proportion of patients prescribed eVTEp following surgery for gynecologic, hepatobiliary, and colorectal cancers by a 30% absolute increase. Methods: We performed an interrupted time series study using quality improvement methodology. Postoperative order sets, pre‐printed prescriptions, process checklists, and multimodal education were introduced. Process and outcome data were collected and analyzed on statistical process control charts. Results: We included 324 patients with gynecologic and hepatobiliary cancers. Despite efforts to include them, the colorectal team did not participate. The monthly mean order set‐use was 58% ( SD  = 14%), by specialty: gynecology 79%, hepatobiliary 47%. The proportion of patients prescribed eVTEp increased from 3% to 70% ( SD  = 14%). The target goal was surpassed and sustained by both cohorts. Patient compliance was 73% ( n  = 117/160, SD  = 16%). Of those who stopped eVTEp early, 45% ( n  = 14/31) objected because of the injectable nature. Bleeding events were infrequent (0.6%, n  = 2/324). Conclusions: Three process changes and multimodal education resulted in a significant increase in eVTEp use. Failure to identify improvement champions limited project expansion to colorectal patients. Patient compliance was largely limited by the injectable nature of the medication.